The process of the influence of interlingual contacts on the mutual enrichment of languages - Almammadova, Sabina; Rzayeva, Nuriyya (My University, 2025)
The mutual enrichment of Azerbaijani through language contact has intensified in the wake of globalization and the nation’s post‑independence integration into international scientific, technical, and diplomatic networks, highlighting the critical role of interlinguistic relations in vocabulary expansion and structural adaptation. Despite extensive descriptive accounts of borrowing phenomena, there is a conspicuous lack of unified, quantitative frameworks that address both general and field‑specific terminologies, particularly regarding the systematic adaptation of European‑sourced technical terms and their phonological and morphological integration. This study therefore investigates how interlanguage contact has shaped Azerbaijani terminology by combining sociolinguistic, ethnolinguistic, and psycholinguistic approaches: we classify typologies of bilingualism (coordinative vs. subordinate; individual vs. collective; receptive vs. produc‑ tive), delineate direct vs. mediated borrowing pathways, and assess standardization practices in both centralized and specialized domains. Our analysis reveals that lexical borrowings first permeate the vocabulary layer, filling semantic gaps through two primary methods—direct transfer and transfer via a third language—and that since independence, European technical and international‑relations terms have undergone formal assimilation to Azerbaijani phono‑mor‑ phological norms, while field terminologies remain dynamic repositories of neologisms. These findings underscore the necessity of conscious, policy‑driven regulation to eliminate terminological variability in the general lexicon without stifling innovation in specialized fields. Therefore, we recommend the development of a comprehensive classification and standardization framework—anchored in corpus‑based computational tools—to monitor borrowing diffusion, guide evidence‑based terminology governance, and inform future language‑planning initiatives.
Keywords: Standardization; Structure; Terminology; Unification; International words